Respostas
respondido por:
1
-3+5/3
cara ai vc tira o mmc de (1 e de 3) = 3
ou multiplicar em cruzes mantendo o denominador quado for sempre esse caso
-9+5/3
-4/3
é nois mano
cara ai vc tira o mmc de (1 e de 3) = 3
ou multiplicar em cruzes mantendo o denominador quado for sempre esse caso
-9+5/3
-4/3
é nois mano
respondido por:
0
- 3 + 5 = 3.(-3) + 5 = - 9 + 5 = - 4
----- -------------- --------- -----
3 3 3 3
Resp.: - 4/3
----- -------------- --------- -----
3 3 3 3
Resp.: - 4/3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás